SOSIALISASI PEMBUATAN AKUN GRABFOOD SEBAGAI UPAYA MENINGKATKAN PENJUALAN TINK ONE DRINK SAKTI LUBIS - Enjellina Br. Simanjuntak; Juli Meliza; Ratu Valana Dewi; Roni Marpaung (Jurnal Pengabdian Pada Masyarakat METHABDI, 2022)
Tink One Drink is a community that is located on Jalan Sakti Lubis, Medan Kota District, Medan City. This business has been run by its owner since 4 years ago. Tink One Drink sells various types of drinks, the most dominant type of drink sold is coffee type drinks. The result of this activity is increasing the sales of Tink One Drink through the application of the Grabfood account